2010
DOI: 10.1002/jpln.200900351
|View full text |Cite
|
Sign up to set email alerts
|

Soil base saturation affects root growth of European beech seedlings§

Abstract: To assess the potential effects of Al toxicity on the roots of young European beech (Fagus sylvatica L.), seeds were sown in soil monoliths taken from the Ah and B horizons of forest soils with very low base saturation (BS) and placed in the greenhouse. The Ah horizons offered a larger supply of exchangeable cation nutrients than the B horizons. After 8 weeks of growth under optimal moisture conditions, the seedlings were further grown for 14 d under drought conditions. Root‐growth dynamics were observed in rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To measure the root elements, the dissolved samples are determined using inductively coupled plasma–optical emission spectrometry (ICP–OES). This technique has multielement and high‐throughput options (Al, B, Ba, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, P, Pb, S, Zn are in a good range; Cd, Co, Mo are usually below the detection limits) (A. K. Richter et al ., 2011 ). As the measurement of P requires ample amount of dried root material, this may not be realistically measured on separate root orders.…”
Section: Root Chemistrymentioning
confidence: 99%
“…To measure the root elements, the dissolved samples are determined using inductively coupled plasma–optical emission spectrometry (ICP–OES). This technique has multielement and high‐throughput options (Al, B, Ba, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, P, Pb, S, Zn are in a good range; Cd, Co, Mo are usually below the detection limits) (A. K. Richter et al ., 2011 ). As the measurement of P requires ample amount of dried root material, this may not be realistically measured on separate root orders.…”
Section: Root Chemistrymentioning
confidence: 99%
“…Al concentrations in the fine roots of common temperate and boreal woody species usually exceed the limit for being hyperaccumulators (>1 mg g - 1 ). For example fine roots of Abies alba , Castanea sativa , Fagus sylvatica , Picea abies , Pinus cembra , and Pinus montana all have values of 1–10 mg g - 1 DW (Zysset et al, 1996; Brunner et al, 2002; Genenger et al, 2003; Hirano et al, 2006; Richter et al, 2011; see also Table 3 ). All these woody species are ectomycorrhizal, suggesting that ectomycorrhizal structures, such as fungal mantle and Hartig net, further contribute to the accumulation of Al in roots by immobilizing Al in the cell wall of the fungal hyphae (Brunner and Frey, 2000; Heim et al, 2003) or in the fungal vacuoles (Martin et al, 1994).…”
Section: Adaptationsmentioning
confidence: 99%
“…In comparison with the control, higher Al contents in soil did not influence the Al accumulation in needles significantly, probably because Al is predominantly accumulated in roots, while its effect on shoots is only secondary (Chaffai, Marzouk 2009). Richter et al (2011) observed that the differences in the physiological status of beech roots were connected rather with nutrient availability and drought application than with differences in Al 3+ concentrations in the soil solution.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of Al leads to decreasing concentrations of K, Ca and Mg and a decrease of the base cations to Al molar ratio in the soil solution (De Witt et al 2010). The Ca:Al ratio in roots and soils has been used as a useful indicator of the health status in plants and a diagnostic tool for the prediction of potential stress in forest ecosystems (Konôpka, Lukáč 2010;Richter et al 2011).…”
mentioning
confidence: 99%